Subserous Cystic Adenomyosis: A Case Report and Review of the Literature - Xu, Tongtong; Li, Yue; Jiang, Lili; Liu, Qifang; Liu, Kuiran (Frontiers in Surgery, 2022)
Cystic adenomyosis is a rare type of adenomyosis that often occurs in adolescents or women of childbearing age. Due to the few reports of this case, its clinical characteristics have not been clearly established. We treated a 32-year-old married patient with cystic adenomyosis that reported persistent abdominal pain and massive vaginal bleeding, so an emergency laparotomy was performed. The intraoperative findings and postoperative pathology proved that the diagnosis was correct. The prognosis of the patient is good, and there is no recurrence within three months after surgery.Surgery is the most effective way to treat cystic adenomyosis. Ultrasound and magnetic resonance are the most effective auxiliary examinations for diagnosing the disease.Cystic adenomyosis is a sporadic disease. This article summarizes this condition’s clinical manifestations, pathological features, diagnosis, treatment, and prognosis by reviewing the existing literature and the case presented in this report. It is noteworthy that early diagnosis and individualized treatment strategies can improve patients' quality of life